2020
DOI: 10.1002/qj.3826
|View full text |Cite
|
Sign up to set email alerts
|

Increasing heavy rainfall events in south India due to changing land use and land cover

Abstract: Through an analysis of land use and land cover (LULC) data for the years 2005 and 2017 from the Advanced Wide Field Sensor onboard the Indian Remote Sensing satellite, we find considerable changes in the LULC in three major states of south India, namely, Tamil Nadu, Telangana and Kerala. This change is mainly due to increasing urbanization, in addition to the change of prevalent mixed forest into deciduous needle/leaf forest in Kerala. Motivated by this finding, we study the impact of these LULC changes over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 53 publications
2
23
2
Order By: Relevance
“…Previous studies suggested that the moisture transport from BOB and its convergence under the persistent synoptic low‐pressure trough caused the heavy rainfall (Chakraborty, 2016; Narasimhan et al., 2016; Srinivas et al., 2018). Also the recent studies (Boyaj et al., 2020) on urban impacts on Chennai heavy rainfall emphasized the role of enhanced thermal transport and ignored the role of urban‐induced roughness and the associated physical processes in the simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the moisture transport from BOB and its convergence under the persistent synoptic low‐pressure trough caused the heavy rainfall (Chakraborty, 2016; Narasimhan et al., 2016; Srinivas et al., 2018). Also the recent studies (Boyaj et al., 2020) on urban impacts on Chennai heavy rainfall emphasized the role of enhanced thermal transport and ignored the role of urban‐induced roughness and the associated physical processes in the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies analyzed the consequences of urban expansion and induced land use changes on extreme rainfall scenarios over tropical Indian cities (Boyaj et al, 2020;Kishtawal et al, 2010;Mohan & Kandya, 2015;Paul et al, 2018). Kumar et al (2008) showed that the highly localized heavy rainfall event (August 2005) over Mumbai was produced as a result of the interaction of synoptic-scale low-pressure system with the typical mesoscale land surface features of this region.…”
mentioning
confidence: 99%
“…Any changes in the average seasonal rainfall patterns have a profound effect on agriculture, and therefore the livelihood of 1.5 billion people in South Asia (Gadgil and Rupa Kumar, 2006). The Indian summer monsoon rainfall (ISMR) is weakening over several regions (e.g., Krishnan et al, 2020), with a simultaneous increase in the extreme events in the recent ∼150 years (Boyaj et al, 2020, and the references therein). Observation-based studies in the last 50-100 years suggest that, on interannual time scales, tropical oceanic phenomena such as the ENSO dominantly influence the ISM variability (see Webster et al, 1998, and the recent reviews by Ashok et al, 2019;Mohanty et al, 2020, and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The extreme weather event during August 2018 in Kerala was attributed to anomalous weather conditions rather than the warming trend in the atmosphere by . Modi cations in the land cover resulted in higher surface temperatures, sensible heat ux, and a deeper and moist boundary layer, resulting in heavy precipitation (Boyaj et al 2020). According to Viswanadhapalli et al ( 2019), high convective instability, offshore vortex, moisture transport from mid-troposphere due to horizontal wind shear and mid-tropospheric moisture transport from the Bay of Bengal played major roles in the extreme precipitation event.…”
Section: Introductionmentioning
confidence: 99%